Early intervention in psychosis programs in Africa, Asia and Latin America; challenges and recommendations - Els van der Ven; Xinyu Yang; Franco Mascayano; Karl J Weinreich; Eric YH Chen; Charmaine YZ Tang; Sung-Wan Kim; Jonathan K Burns; Bonginkosi Chiliza; Greeshma Mohan; Srividya N Iyer; Thara Rangawsamy; et al. (Cambridge Prisms: Global Mental Health)
Abstract